Between sacrum and profanum: the relationship of religious freedom and the freedom of art in the jurisprudence of the ECHR - Banaś, Hanna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
Formerly, art was closely connected to religion. Nowadays, art is such a far-reaching, controversial phenomenon, that the recipient no longer knows what he is looking at. Religion (as an aim) is a great example. It applies to the most intimate sphere of the individual’s life and it is difficult to legally regulate this issue. There is no definition of art, nor of religion, which is sufficiently precise to be a basis for judgments. The European Court of Human Rights has partly dealt with this matter in its judgments but this is still not enough to solve the problem.